1988
DOI: 10.1080/07315724.1988.10720263
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenic response to an oral glucose load in man: comparison between young and elderly subjects.

Abstract: To investigate the effect of age and change in body composition on the increase in energy expenditure consecutive to the ingestion of a 75-g glucose load, respiratory exchange measurements were performed on 24 subjects, 12 elderly (mean +/- SEM, 73 +/- 1 yr) and 12 young (25 +/- 1 yr). The body weight was comparable, 62 +/- 2 kg in the elderly group vs 61 +/- 3 in the young, but the body fat content of the elderly group was significantly greater than that of the young (29 +/- 2% vs 19 +/- 2%, p less than 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The first 120 min were allocated for isotopic equilibration. Thereafter, 1 g/kg of naturally 13 Cenriched corn starch glucose was ingested.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first 120 min were allocated for isotopic equilibration. Thereafter, 1 g/kg of naturally 13 Cenriched corn starch glucose was ingested.…”
Section: Subjectsmentioning
confidence: 99%
“…Plasma and ingested 13 C glucose isotopic enrichment was measured by gas chromatography-combustion-isotope ratio mass spectrometry (Sira 12, VG Instrument, Middlewich, UK) [18]. 13 C enrichment of expired CO 2 was determined with isotope ratio mass spectrometry [19].…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is associated with negative consequences among the elderly, such as loss of functional capacity and autonomy (Fleg and Lakatta 1988;Baumgartner et al 1998;Lima et al 2009), increased risk of falls (Whipple et al 1987), metabolic impairments (Bloesch et al 1988), and reduced bone mineral density (Gentil et al 2007a(Gentil et al , b, 2009Lima et al 2009). Previous reports provide evidence that sarcopenia has significant health-care cost implications that warrant efforts to understand and counteract this age-related muscle mass and strength decline (Janssen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the consequences of natural ageing is the decline of several physiological functions, which expose the elderly to greater frailty and loss of autonomy 2 . Particularly, the muscle system undergoes changes, such as the decrease of strength and mass 3,4 (a process called sarcopenia), which is seen in both men and women 5 and may be associated with loss of autonomy, risk of falls 6 , metabolic complications 7 , reduction of mineral bone density 8 and decline in aerobic capacity 9 . Previous studies showed that the effects of sarcopenia raise healthcare costs 10 , which stresses the importance of avoiding or delaying the loss of strength and muscle mass during ageing.…”
Section: Introductionmentioning
confidence: 99%